Technology, isolation, and drug use: a social network analysis of suicide risk - García-Jarquín, Brenda; Aguilar-Fernández, Mario; Sanchez-Medina, Marco Antonio; García-Montalvo, Iván Antonio; López-Ramírez, Enrique (Frontiers in Education, 2025)
The purpose of this study is to identify the most influential variables in suicide among students, based on studies conducted from 2019 to 2024. Given the increase in suicide rates within this demographic group, 26 variables were identified, analyzed, and modeled in a social network. Indices of density, centrality, and closeness were used to assess the influence of each variable within the network. The results showed that the use of technologies, isolation, depression, and repeated exposure to traumatic experiences increase suicidal ideation and, therefore, the risk of suicide. These findings emphasize the need to develop multifaceted prevention programs tailored to student populations for more effective outcomes.